2010
DOI: 10.1186/1471-2121-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II upregulates the expression of placental growth factor in human vascular endothelial cells and smooth muscle cells

Abstract: BackgroundAtherosclerosis is now recognized as a chronic inflammatory disease. Angiotensin II (Ang II) is a critical factor in inflammatory responses, which promotes the pathogenesis of atherosclerosis. Placental growth factor (PlGF) is a member of the vascular endothelial growth factor (VEGF) family cytokines and is associated with inflammatory progress of atherosclerosis. However, the potential link between PlGF and Ang II has not been investigated. In the current study, whether Ang II could regulate PlGF ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
4
40
0
Order By: Relevance
“…6,7 Third, because the expression of PlGF in vascular cells is enhanced by angiotensin II and aldosterone, PlGF is thought to be a downstream target of the renin-angiotensin system (RAS) and mineralocorticoid receptor. [31][32][33] In CKD, there is isolated or synergistic RAS and mineralocorticoid receptor hyperactivity, which is possibly mediated by upregulation of PlGF. 34,35 Further clinical research is needed to investigate the association between PlGF levels and RAS.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Third, because the expression of PlGF in vascular cells is enhanced by angiotensin II and aldosterone, PlGF is thought to be a downstream target of the renin-angiotensin system (RAS) and mineralocorticoid receptor. [31][32][33] In CKD, there is isolated or synergistic RAS and mineralocorticoid receptor hyperactivity, which is possibly mediated by upregulation of PlGF. 34,35 Further clinical research is needed to investigate the association between PlGF levels and RAS.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time PlGF has been described to be expressed in adult endothelial cells as well as smooth muscle cells [17]. Hence, serum levels of PlGF in pregnant women are a combination of secretion/release from different trophoblast populations in combination with secretion/release from different maternal vascular cells.…”
Section: Plgf: An Early Marker For Preeclampsia?mentioning
confidence: 99%
“…7-9 Recent studies have shown that UII and Ang II may induce vascular remodeling in the adventitia by inducing the differentiation, migration and proliferation and collagen synthesis in adventitial fibroblasts. 3, 10 The above effects are mainly achieved through the binding of UII and Ang II with their respective receptors to activate downstream pathways such as mitogen-activated protein kinase (MAPK), protein kinase C (PKC) and calcium channels. 3 However, the exact mechanisms by which UII and Ang II mediate vascular remodeling in the adventitia are still largely unclear.…”
mentioning
confidence: 99%
“…10 Jin et al found that Flt-1 was expressed in adventitial fibroblasts; however, little is known about whether adventitial fibroblasts serve as a novel source of VEGF. 17 The effects of Ang II and UII on VEGF expression have been mostly studied in vascular endothelial cells and smooth muscle cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation